Potentials of immunonutrition in wound healing : a review - Yap, Wei Boon; Nur Farhana Azizan,; Elynna Azura Hasnol,; Kavipriya Krishnan,; Sivanesan Rajeswaran,; Jia, Yin Chow; Noraihan Irwan,; Pavitra Indrajoth,; Pramila Mani, (Penerbit Universiti Kebangsaan Malaysia, 2022)
A delayed wound healing process can lead to detrimental complications in chronic wound patients such as tissue necrosis and systemic infections. Application of immunonutrition (IN) in experimental animal models and chronic wound patients has shown promising and improved wound healing processes. IN restores the supply of essential nutrients that are critical for cell growth and tissue repair in the wounded subjects. Several commonly found nutrients in IN formulations include polyunsaturated fatty acids (PUFAs), essential amino acids, trace elements such as zinc and vitamins. Recently, some studies suggested the use of traditionally used herbs like curcumin in IN recipes due to its efficient wound healing properties. The roles and functions of IN in wound healing encompass recruitment of white blood cells, platelets and fibroblasts into the wounded area during the coagulation and inflammation phases, enhancement of fibroblast proliferation, collagen synthesis and neovascularization in the proliferation phase; and lastly, regulation of tissue re-epithelization for wound closure and recovery. In this review, the roles and functions of individual nutrients were deliberately discussed alongside their mechanisms of action in wound healing. This aims to provide a more holistic insight into the potentials of those nutrients when used as part of IN for major wound patients. Despite its remarkable effects in wound healing, several criteria should be considered in an IN formulation: the type and severity of wounds, administration timing and mode of administration, and concoction of immune-boosting nutrients in order to ensure the optimal wound healing effects.